Pengaruh Perbedaan Jenis Umpan Alat Tangkap Pancing Ulur (Handline) terhadap Hasil Tangkapan di Perairan Muncar Banyuwangi Jawa Timur - Jessica Jessica; Yusrudin Yusrudin; Exist Saraswati (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2024)
Line fishing consists of several components, namely 1) reel; 2) fishing line; 3) fishing line; and 4) weight. Line fishing business in its development has not experienced much significant progress when compared to other fishing gear. To overcome this, various efforts and modifications were made to optimize the productivity and effectiveness of this fishing gear. In addition, the use of fishing rods with various sizes and types as well as modification of various kinds and forms of artificial bait for fishing effectiveness is relatively less applied by handline fishermen.The purpose of this study is to determine the effect of the use of different types of artificial bait on fish catches, to determine the interaction between the differences in the use of different types of artificial bait in fishing gear during fishing operations. The research method that will be carried out is the experimental fishing method, namely the method by participating in fishing operations using hand line fishing gear that will be given three different types of artificial bait. The artificial baits used are chicken feathers, goldfish thread and pentil.